DETEKSI FORMALIN DALAM MAKANAN DENGAN INDIKATOR ALAMI DARI EKSTRAK BUNGA TELANG (CLITORIA TERNATEA L.) - Yuliantini, Anne (STIKes Bakti Tunas Husada, 2018)
Anthocyanin is a plant dye that can change in the presence of protein. Formalin-containing foods such as fish, chicken, wet noodles, and tofu have proteins that can methylene bond with formalin so that the protein becomes damaged. Anthocyanin color will be change if added to proteins that contain formalin and only protein because proteins are able to change and stabilize anthocyanin color. This study aims to detect the presence of formalin in foods with telang flower extract (Clitoria ternatea L.) which contains high levels of blue anthocyanins. The method used in this study is the result of visual observations assisted by visible spectrophotometer and confirmed by chromatropic acid method. The results showed that the flower extract of telang ethanol was able to detect formalin in food by not showing discoloration when added with telang flower extract which gradually turned into greenish ash while for the negative color results it was stabilized green turkey with a limit of detection of fish, chicken, wet noodles , and know, respectively 1.9654; 1,6987; 2,2514; and 1.5821 mg / g, with a SBR value of 10.845; 9,372; 22,625; and 5.908%. From the results of testing the samples with telang flower extract showed 4 positive samples while the chromatropic acid method 6 positive samples contained formalin.